Age and gender differences in self‐control and its intergenerational transmission. (2nd October 2016) - Wang, L.; Fan, C.; Tao, T.; Gao, W.
Abstract: Background: Few studies have been conducted in people of Asian descent that have reported to demonstrate the distinct developmental trends in good self‐control and poor control. To fill this gap, we conducted a national cross‐sectional survey among adolescents and young adults in China to further clarify the age and gender differences in self‐control from a dual‐systems perspective. Methods: A total of 2910 adolescents (female, n  = 1698) and their parents from five different provinces in China were surveyed using the Dual‐Modes of Self‐Control Scale (DMSC‐S) and the Parents' Perceived Self‐Control Scale. The mean age of the adolescent sample was 17.47 years (ranging from 12.50 to 25.42 years). Results: Boys exhibited greater good self‐control than girls. Poor control increased between 12 and 17 years of age and declined thereafter; however, good self‐control increased over the entire study period. Both good self‐control and poor control in student participants were significantly associated with parents' perceived self‐control; moreover, the association between good self‐control and parental self‐control was mediated by SES. Conclusion: The roles of age, gender, parental self‐control and SES varied in a dual‐systems model of self‐control: good self‐control and poor control. Implications of these results are discussed.